Are Multidimensional Pain Inventory Coping Strategy Profiles Associated with Long-Term Spinal Cord Stimulation Effectiveness?. Issue 5 (26th May 2017) - Paroli, Mery; Bernini, Olivia; De Carolis, Giuliano; Tollapi, Lara; Bondi, Franca; Martini, Antonella; Dario, Alessandro; Paolicchi, Adriana
Abstract: Introduction: It is acknowledged that the way patients cope with pain may influence treatment outcome. In particular, psychological factors are deemed important when considering patients for suitability for spinal cord stimulation (SCS). Objective: The aim of the study is to observe how pre-implantation psychological characteristics impact the effectiveness of SCS for chronic pain. Methods: The analysis comprised data from 137 patients who underwent an SCS implant. Screening evaluation included a coping strategies profile (Multidimensional Pain Inventory) and psychiatric disorders (Mini-International Neuropsychiatric Interview). Based on SCS implant outcome collected during follow-up visits, patients were divided into three groups: subjects with long-term pain relief (long-term group), subjects who failed the SCS treatment and decided to explant trial device (trial explanter group [TE]), and those who chose a permanent device (permanent explanter group [PE]). Results: Results showed that most of the patients who failed with the SCS (TE and PE groups) demonstrated a dysfunctional coping profile and showed a higher presence of psychiatric disorders, which significantly influenced the experience and perception of pain. Conclusions: The findings of this study support the value of a multidisciplinary screening. Addressing psychological issues before SCS implantation can reduce the failure rate of SCS.